1970
DOI: 10.1080/00288233.1970.10421205
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of spermatozoa in the reproductive tract of the Romney ewe

Abstract: The ampulla, isthmus, uterus, and cervix of mixed-age Romney ewes were examined for the presence of spermatozoa 1, 2, 4, 8, 16, 24, 36, and 48 hrs after a single mating. Spermatozoa were recovered from the following sites at the stated intervals after copulation: the cervix 1 hr, the uterus 2 hrs, the isthmus 4 hrs, and the lower ampulla 16 hrs. Peak numbers in all regions occurred 16 hrs after mating. Cervical numbers were noticeably constant up to 16 hrs and then began to fall.Spermatozoa disappeared rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…This result is consistent with those of Mattner (1963), Quinlivan & Robinson (1967 and Lang & Oh (1970), who found that 16 to 24 hr after mating or insemination, the accumulation in the oviduct of spermatozoa which are gradually released from the cervical reservoir (Quinlan, Mare & Roux, 1933;Mattner, 1963Mattner, , 1966 is at a maximum. When restricted sperm doses are used, inseminations carried out too early result in exhaustion of the sperm reserve before ovulation has taken place, which coincides, on average, with the end of oestrus in sheep (McKenzie & Terrill, 1937;.…”
supporting
confidence: 93%
“…This result is consistent with those of Mattner (1963), Quinlivan & Robinson (1967 and Lang & Oh (1970), who found that 16 to 24 hr after mating or insemination, the accumulation in the oviduct of spermatozoa which are gradually released from the cervical reservoir (Quinlan, Mare & Roux, 1933;Mattner, 1963Mattner, , 1966 is at a maximum. When restricted sperm doses are used, inseminations carried out too early result in exhaustion of the sperm reserve before ovulation has taken place, which coincides, on average, with the end of oestrus in sheep (McKenzie & Terrill, 1937;.…”
supporting
confidence: 93%
“…This time-scale is even more rapid than has been previously inferred from reports of significant numbers of spermatozoa being recovered from the cervix at varying times from 15 min to 2 h after insemination (e.g. Mattner 1963a; Quinlivan and Robinson 1969;Lang and Oh 1970;Lightfoot and Salamon 1970;Hawk and Conley 1975;Croker et al 1975). Also, Quinlivan and Robinson (1967) claimed that cervical reservoirs are established within 1 h of insemination.…”
Section: Discussionmentioning
confidence: 68%
“…Hence the chances of conception will be dependent on the speed of establishment of an adequate population of spermatozoa in the cervix. The speed that such a population is established in the ewe is unknown although it is likely to be within a few hours of mating because large numbers of spermatozoa have been reported in the cervix from 15 min to 2 h after mating or insemination (Mattner 1963a; Quinlivan and Robinson 1969;Lang and Oh 1970;Lightfoot and Salamon 1970;Hawk and Conley 1975;Croker et al 1975). During the period required to establish an adequate cervical population of spermatozoa the vagina must act as a reservoir for spermatozoa.…”
Section: Introductionmentioning
confidence: 99%